Purificação de eliciadores de defesa vegetal em soja e feijoeiro a partir de nematoides fitopatogênicos - Trevisoli, Edilaine Della Valentina Gonçalves (2016)
The induction of resistance in plants to pathogens is an alternative method of disease control, wich involves activation of plant resistance mechanisms such as induction of phytoalexins. The elicitors molecules are able to induce and activate those responses, and therefore, techniques have sought to isolate and characterize fractions with elicitor character. The study aimed to purify, through ion exchange chromatography and gel filtration chromatography, eliciting molecules from pathogenic nematodes, and test them in phaseolin induction in beans hypocotyls beans and gliceolin in soybean cotyledons. The buffer solution Tris HCl 0.05 M (pH 6.8) was used as control and the acibenzolar-S-methyl (50 mg a.i. L-1) and Saccharomyces cerevisiae (20 mg mL-1) were used as induction standard treatments. Ion exchange chromatography (IEC) and gel filtration chromatography (GC) were performed to separate fractions with eliciting power from 500 female nematodes of Meloidogyne incognita and Meloidogyne javanica. For purification of elicitors from Meloidogyne javanica, through IEC, six glycidic fractions and six glycoproteins were obtained. These were purified on GC, obtaining sixty-three fractions. They have been classified according to their nature, as twenty-six glycidic and thirty-seven glycoprotein with molecular weights ranging from 29.19 to 2989.25 kDa. Regarding the elicitors purification of Meloidogyne incognita through IEC, nine glycidic and five glycoprotein fractions were obtained. From these fractions, a total of fifty-eight fractions was obtained through GC, twenty-five glycidic and thirty-three glycoprotein with molecular weights ranging from 37.42 to 200.32 kDa. From the fractions purified from Meloidogyne javanica eight had inducing potential of phaseolin. For gliceolin fifteen fractions showed inducing effect. Regarding the fractions purified from Meloidogyne incognita, no fraction has inductive potential of phaseolin superior to the standard treatment. However, twenty-two fractions suppressed phytoalexin inducing activity. For gliceolin ten fractions induced the same, whereas, twenty-three fractions suppressed the induction of gliceolin. Chromatography was efficient in the purification of elicitors compounds. Compounds with suppressing characteristics of gliceolin and phaseolin were checked in bioassays. For those fractions obtained through IEC, and then submitted to GC that did not induce phytoalexin, it is suggested that molecules need to act together to have elicitor effect and thus induce defense response in the plant